(3GdUMjaI GdSLGOjIs - (3GdbQTj GdgGTej, CHh GdMSf, Rjf GdYGHOjf, Ydj Hf GdMSjf Hf Ydj Hf CHj WGdH, (B94(3g`s ((3GdeTgO GdQVhjs)
(3ChdgG (B:s
(3MOKfG GdSjO GdCLd fLe GdOjf bGd CNHQfG GdTjN GdSYjO CHh YHO Gddg (B...(3GdNGRf dNRGfI ehdGfG CejQ GdeDefjf Ydj Hf CHj WGdH aj TgQ QHjY GdChd ef SfI SJI YTQ hNeS eFI bQGAI Ydjg hCfG CSeY(B... (3Yf CHjg eJhcd Hf gGQhf bGd dbjJ jMji Hf RjO Hf Ydj hgh eJhLg Edi NQGSGs
(3BNQgG (B:s
(3hdG JhMT Hj Cgd CfSj hJJe EMSGfc ajeG Hbj ef YeQj ceG CMSfJ Edj ajeG eVi(B...s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B:4(3, U(B277s
(3GdPQjYI(B: (3L(B13(3, U(B342s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs